2023
DOI: 10.1099/ijsem.0.005865
|View full text |Cite
|
Sign up to set email alerts
|

Cystofilobasidium josepaulonis sp. nov., a novel basidiomycetous yeast species

Abstract: A yeast strain belonging to the basidiomycetous yeast genus Cystofilobasidium was isolated from a marine sediment sample collected in an intertidal zone in Shandong province, PR China. The results of phylogenetic analyses based on sequences of the D1/D2 domain of the 26S ribosomal RNA gene and the internal transcribed spacer (ITS) region indicate that this strain, together with three other strains isolated from basal ice collected in Norway, the gut of an insect and an alga collected in Russia, represent a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In this study, we obtained 286 yeast species, including 140 ascomycetous and 146 basidiomycetous species associated with intertidal zones of China (Table S2). Boekhout et al (2022) summarized that at least 782 yeast species have been recorded from China recorded until 2020 and 49 additional yeast species were reported from China in the past three years (Gao et al, 2021;Shi et al, 2021;Chai et al, 2022a;Chai et al, 2022b;Chai et al, 2022c;Chu et al, 2022;Li et al, 2022;Wei et al, 2022;Chai et al, 2023;Liu et al, 2023;Qiao et al, 2023;Yu et al, 2023;Zhu et al, 2023a;Zhu et al, 2023b). The number of yeast species discovered in this study accounts for 34.7% in the total yeast species that have been found from China, indicating that there are abundant resources of culturable yeasts in the intertidal zones of China.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study, we obtained 286 yeast species, including 140 ascomycetous and 146 basidiomycetous species associated with intertidal zones of China (Table S2). Boekhout et al (2022) summarized that at least 782 yeast species have been recorded from China recorded until 2020 and 49 additional yeast species were reported from China in the past three years (Gao et al, 2021;Shi et al, 2021;Chai et al, 2022a;Chai et al, 2022b;Chai et al, 2022c;Chu et al, 2022;Li et al, 2022;Wei et al, 2022;Chai et al, 2023;Liu et al, 2023;Qiao et al, 2023;Yu et al, 2023;Zhu et al, 2023a;Zhu et al, 2023b). The number of yeast species discovered in this study accounts for 34.7% in the total yeast species that have been found from China, indicating that there are abundant resources of culturable yeasts in the intertidal zones of China.…”
Section: Discussionmentioning
confidence: 51%
“…Compared to the studies on terrestrial environments, only limited studies focused on yeasts in marine environments in China. Yang et al (2011); Chi et al (2012); Zhu et al (2023a), andZhu et al (2023b) described some known and novel marine yeast species in diverse marine environments of China. Wang et al (2017) found one marine yeast strain which possesses the capability for biodiesel production from renewable feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al [69] found that Curvibasidium sp. Y231 showed optimal growth at 20 • C. The maximum growth temperature of Cystofilobasidium josepaulonis is 28 • C, and the optimal growth temperature is 17-20 • C [70]. Therefore, we speculated that rising temperatures were the main reason that led to the almost disappearance of Curvibasidium and Cystofilobasidium during 13 weeks of deterioration.…”
Section: Function Of Fungimentioning
confidence: 95%